PENANGGULANGAN PERDAGANGAN ORANG DALAM (INSIDER TRADING) DI BIDANG PASAR MODAL DITINJAU DARI PERSPEKTIF HUKUM PIDANA - Mahayani Dewi, Ida Ayu Nyoman; Suarbha, I Wayan (Kertha Wicara : Journal Ilmu Hukum, 2014)
Combating the insider trading in stock market seen from the criminal law perspective which discusses the regulatory framework and its criminal liability pursuant to Penal Code Draft in the near future. Method applied shall be normative legal research considering the vagueness of norm. The purpose of this journal is to acknowledge the regulation of insider trading based on the future Penal Code Draft. Several regulations concerning insider trading namely, as follows: Indonesian Penal Code (KUHP) and Law No. 8 Year 1995 concerning Stock Market (UUPM). However, aforementioned laws had been considered weak and unable to combat the development of insider trading in Indonesia. Aside from that, Indonesian Penal Code had not regulated the act of plagiarism onto its provisions. From the statement above it can be concluded that the regulation regulated the insider trading is not yet able to combat this crime. Thus, criminal law reform is urgently needed in order to combat insider trading in Indonesia.
Keywords: Stock Market, insider trading, combating effort, criminal law reform